Transnasal Percutaneous Endoscopic Gastrostomy (T-PEG): An Alternative Approach to Conventional PEG Placement - KV, Anudeep; Kalapala, Rakesh; Darishetty, Santosh; Katamreddy, Thejesh; Reddy, N. D. (Journal of Digestive Endoscopy, 2021)
Transnasal percutaneous endoscopic gastrostomy (T-PEG) is a novel endoscopic intervention for enteral nutrition. Peroral endoscopic gastrostomy is widely performed feeding procedure. However, it cannot be done in 4 to 7% of cases with head & neck malignancies. T-PEG is a safe and viable alternative procedure in those patients. T-PEG can be performed in patients with head and neck malignancies, malignant oropharyngeal obstruction, and trismus where oral endoscopy is not feasible.
Keywords: head and neck malignancy; percutaneous endoscopic gastrostomy; T-PEG